QoS analysis of video streaming service in live cellular networks - Díaz-Zayas, Almudena; Merino-Gómez, Pedro; Rivas Tocado, F. Javier (Elsevier, 2010)
The increasing computing and communication power of new terminals in mobile networks has converted these smart phones into Internet hosts. They can be used for traditional services, such as browsing or e-mailing, but also as platforms for specific new IP multimedia services like Push to Talk, streaming or IPTV. However, developing new services or porting existing popular ones should be done considering the target network in which the services will be deployed. This paper presents an analysis of video streaming, a service with real time requirements, on live mobile networks to validate current deployments. In this analysis we propose using smart phones as measurement devices in a way that enables them to capture customers’ experiences. An outstanding contribution of this paper is that real measurements are carried out in real networks, with real transmission power, real antennas and real network operators and protocol stacks. These measurements help to complete performance results obtained in simulations and emulations carried out in laboratories.
Keywords: Tecnología Streaming; Streaming; Mobile network; Performance; Testing